1984
DOI: 10.1126/science.6147018
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Distribution of Dopamine Receptor Densities in Brains of Schizophrenics

Abstract: The dopamine hypothesis of schizophrenia was examined by measuring the density of dopamine receptors in the postmortem brains of 81 control subjects and 59 schizophrenics from four different countries. The densities of dopamine receptors in the tissues from the schizophrenic patients had a bimodal distribution in the caudate nucleus, putamen, and nucleus accumbens. One mode occurred 25 percent above the control density, and a second mode occurred at a density 2.3 times that of the control density for all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
85
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(96 citation statements)
references
References 15 publications
10
85
0
1
Order By: Relevance
“…Is it possible that the one third of schizophrenic patients without elevated dopamine levels are the same one third who tend to develop dysphoric responses during antipsychotic drug therapy? Our study supports a growing notion that dopaminergic function may differ vastly, across different people with schizophrenia (Seeman et al 1984;Zakzanis and Hansen 1998), and at different stages of illness (Laruelle et al 1999), but also indicated that schizophrenic patients with little or no elevation of synaptic dopamine at the baseline were indeed at an increased risk to experience dysphoric responses with AMPT.…”
Section: Discussionsupporting
confidence: 73%
“…Is it possible that the one third of schizophrenic patients without elevated dopamine levels are the same one third who tend to develop dysphoric responses during antipsychotic drug therapy? Our study supports a growing notion that dopaminergic function may differ vastly, across different people with schizophrenia (Seeman et al 1984;Zakzanis and Hansen 1998), and at different stages of illness (Laruelle et al 1999), but also indicated that schizophrenic patients with little or no elevation of synaptic dopamine at the baseline were indeed at an increased risk to experience dysphoric responses with AMPT.…”
Section: Discussionsupporting
confidence: 73%
“…In other words, those patients who have lower dopamine functioning are the ones who are vulnerable for dysphoric responses when further given potent dopamine blocking antipsychotics. This observation has also clarified why not all persons with schizophrenia develop negative subjective responses on antipsychotic medications, confirming early observations that not all persons with schizophrenia have high dopamine D 2 functioning [28].…”
Section: Neurobiology Of Subjective Tolerability To Antipsychotic Medsupporting
confidence: 65%
“…Dopaminergic nigrostriatal pathway has a role in movement control, so the study of the dopamine transporter (DaT) may be of great value to determine its effect in the appearance of Drug-induced parkinsonism [8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%